Impossible to Prove - Nielsen, Philippa (Auckland University of Technology, 2012)
This practice-based research explores the strangeness of the ordinary, through a photographic and sculptural investigation of familiar objects and materials. Photographically, I am looking for slight rifts in the expected. Sculpturally, I use found imagery, readymade objects and craft and office materials to create image-objects that operate in relation to each other as collage in space. I am looking for a transformative interaction of objects and comprehension, in order to examine assumptions of knowledge and create new possibilities in worldview. Like a shift in perception caused by a paradox or a pun, my work is a place to hold mystery and comedy. Each image or object contains a set of personal and cultural references, and I am looking for a multiplication of associations within the spaces between.
Keywords: Sculpture; Photography; Readymade; Collage